2007
DOI: 10.2486/indhealth.45.62
|View full text |Cite
|
Sign up to set email alerts
|

Development and Process Evaluation of the Participatory and Action-Oriented Empowerment Model Facilitated by Occupational Health Nurses for Workplace Health Promotion in Small and Medium-Sized Enterprises

Abstract: The objective of this study is to develop an available empowerment model for workplace health promotion (WHP) in small and medium-sized enterprises (SMEs) and to evaluate its applicability and feasibility. Semi-structured interviews with employers and workers in SMEs were conducted to assess their actual requirements for support. The structure of our new empowerment model was discussed and established through several rounds of focus group meetings with occupational safety and health researchers and practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The two concepts of the hypothesis model such as “building relationship with workers” and “gaining better‐than‐expected results” were extracted each as an integrated factor. This was because the facilitators within the roles of promoting workers' involvement focused on encouraging a strategic approach with the continual action‐oriented process taken by workers and managers as well as the consensus building through each participatory workplace environment improvement program. It is assumed that these outcomes including the strategic aspect with the role of a facilitator who acted to involve workers may relate to the initiative based on good relationships with workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two concepts of the hypothesis model such as “building relationship with workers” and “gaining better‐than‐expected results” were extracted each as an integrated factor. This was because the facilitators within the roles of promoting workers' involvement focused on encouraging a strategic approach with the continual action‐oriented process taken by workers and managers as well as the consensus building through each participatory workplace environment improvement program. It is assumed that these outcomes including the strategic aspect with the role of a facilitator who acted to involve workers may relate to the initiative based on good relationships with workers.…”
Section: Discussionmentioning
confidence: 99%
“…Workers selected to play the role of the key persons in the participatory approach program are called facilitators, and their main function is to sustain the initiative for planning and implementing the participatory work improvement programs and evaluating the outcomes. There are many studies that addressed the roles of the facilitators in the participatory workplace environment improvement programs . However, very few of them mention the changes which occurred to the facilitators as a result of taking part in the participatory approach.…”
Section: Introductionmentioning
confidence: 99%
“…Another review paper on health promotion in SMEs in the USA also revealed that the main barriers on WHP implementation were the inner setting of the enterprises, including few service providers, low commitment, and low internal capacity to implement the program [ 20 , 23 , 24 ]. However, most of these literatures were from the USA or Europe, and the evidence regarding barriers and facilitators that influence multi-level WHP implementation in Asian SMEs is quite limited [ 25 28 ]. Worksite contextual factors, including organizational culture, resources, and structures, and their relationships with WHP implementation may be different across regions and countries.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that organizational cultural factors were related to the effectiveness of organizations in North America, but not in Asian organizations including Japan 22 . However, the evidence regarding WHP implementation in Asian SMEs is quite limited [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%